Utility of RSV rapid diagnostic assays in hospitalized children in Amman, Jordan. Issue 6 (30th October 2020) - Freeman, Megan C.; Haddadin, Zaid; Lawrence, Lindsey; Piya, Bhinnata; Krishnaswami, Shanthi; Faouri, Samir; Shehabi, Asem; Williams, John V.; Khuri‐Bulos, Najwa; Halasa, Natasha
Abstract: Background: Respiratory syncytial virus (RSV) is the leading cause of acute respiratory infections in children worldwide and a frequent cause of hospitalization. Rapid diagnostic assays (RDAs) are available for RSV and they help guide management; however, they are underutilized in developing countries. We compared molecular diagnostics to RSV RDA in hospitalized children in Amman, Jordan. Materials and Methods: Children under 2 years of age, admitted with fever and/or respiratory symptoms were enrolled prospectively from March 2010 to 2012. Demographic and clinical data were collected through parent/guardian interviews and medical chart abstraction. RSV RDAs were performed, and nasal/throat swabs were tested for RSV using quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR). Results: RSV RDA and PCR were performed on specimens from 1271 subjects. RSV RDA had a sensitivity of 26% and a specificity of 99%, with positive and negative predictive values of 98.6% and 43%, respectively. RDA‐positive patients had fewer days of symptoms at presentation and were more likely to have a history of prematurity, lower birth weight, require supplemental oxygen, and a longer hospitalization as compared with subjects with negative RDA. Multivariate analysis showed only lower birth weight, lack of cyanosis on examination, and lower cycle threshold to be independently associated with positive RDA ( p  ≤ .001). Conclusion: RSV RDAs had high specificity, but low sensitivity as compared with qRT‐PCR. Positive RDA was associated with patients with a more severe disease,  as indicated by oxygen use, longer length of stay, and higher viral load. Implementation of RDAs in developing countries could be an inexpensive and expedient method for predicting RSV disease severity and guiding management.